OPTIMALISASI PENGGUNAAN STEEL PLATE SHEAR WALL (SPSW) PADA TOWER MAGNA ONE SURABAYA TERHADAP BEBAN GEMPA - ALFURQAN, SEPTINDRA HAFIZH (Universitas Negeri Surabaya, 2023)
Tower Magna One Surabaya is a building that has two functions: Low Zone Office building and High Zone Apartment with structural reinforcement using CSW in the form of Core Wall. This study analyzes the optimization of the use of SPSW at Tower Magna One Surabaya against earthquake loads. The implementation of the research was carried out by experimental observation using a quantitative approach. Modeling is done using the SAP 2000 V22 program. The results of the addition of the SPSW structure with column stiffeners WF 500x200x10x16 and WF beams 500x200x10x16 provide rigidity to Tower Magna One Surabaya so that the resulting Max Displacement is 40.9 mm smaller compared to CSW of 41.2 mm. The SPSW structure can reduce the Base Shear Reaction in the x and y directions by 60%. The SPSW structure is able to accept greater axial forces compared to CSW. Variation of minimum SPSW plate thickness of 10 mm at Tower Magna One Surabaya. The use of SPSW with SPSW plate thickness of 10 mm is able to provide strength comparable to CSW with a thickness of 50 cm, and SPSW can reduce the mass of the structure by 9.3% compared to CSW. Keywords: CSW, Deviation, Shear Force, SPSW.